Customer Relationship Management and Innovation Capability Affecting Organizational Performance in Automotive Parts Industry, Eastern Economic Corridor - Prasertwong, Natitorn; Wongsansukcharoen, Jedsada (Journal of Business, Innovation and Sustainability (JBIS), 2022)
The aim of this research is to empirically test a framework which identifies effect of customer relationship management and innovation capability that affected organizational performance in automotive parts industry in Eastern economic corridor. The research is quantitative research which was done by survey method using self administered questionnaires. The random samples were collected from 340 peoples who are operating in automotive part industry in EEC. Then all selected data were classified and analyzed by descriptive statistical method such as Frequency, Mean, and Standard Deviation including confirmation factors analysis (CFA) and structural equation modeling (SEM) for hypothesis testing. The result found that the customer relationship management have directly influenced on the organizational performance with coefficient of 0.77 and have directly influenced on innovation capability with coefficient of 0.71. And have an indirectly influenced on the organizational performance through the mediator variable of innovation capability with coefficient of 0.16. Moreover, the innovation capability has directly influenced on organizational performance with coefficient of 0.23, all testing result significantly influenced is 0.001.